Integrated Approach to Anterior Mandibular Cyst Removal and Implant Placement: A Clinical Perspective – Case Report - Mahesh, Lanka; Lahori, Manesh; Bali, Praful; Sushmita (British Journal of Healthcare and Medical Research, 2025)
Background: Edentulous anterior mandibular regions are frequently restored with dental implants. However, underlying lesions may remain undiagnosed on conventional imaging. Case Presentation: A patient presented with an edentulous anterior mandible seeking a permanent prosthetic solution. OPG showed no abnormalities, but CBCT—advised due to anterior mandibular pain—revealed a large radiolucent lesion. The lesion was enucleated, the defect grafted, and reinforced using titanium mesh and collagen membrane. Histopathology confirmed a radicular cyst. After healing, four implants were placed, restoring aesthetics and function. Conclusion: CBCT imaging and a multidisciplinary approach enabled detection, surgical management, and successful prosthetic rehabilitation in a previously unsuspected cystic lesion.